Using fMRI to investigate the potential cause of inverse oxygenation reported in fNIRS studies of motor imagery. (1st January 2020) - Abdalmalak, Androu; Milej, Daniel; Cohen, David J.; Anazodo, Udunna; Ssali, Tracy; Diop, Mamadou; Owen, Adrian M.; St. Lawrence, Keith
Highlights: TR-fNIRS can detect motor imagery activity with good agreement to fMRI. Movement during the rest periods caused activity in the primary motor cortex. This out-of-phase activity may be detected by TR-fNIRS. Hence, partial volume errors may lead to inverse oxygenation in TR-fNIRS. Abstract: Motor imagery (MI) is a commonly used cognitive task in brain–computer interface (BCI) applications because it produces reliable activity in motor-planning regions. However, a number of functional near-infrared spectroscopy (fNIRS) studies have reported the unexpected finding of inverse oxygenation: increased deoxyhemoglobin and decreased oxyhemoglobin during task periods. This finding questions the reliability of fNIRS for BCI applications given that MI activation should result in a focal increase in blood oxygenation. In an attempt to elucidate this phenomenon, fMRI and fNIRS data were acquired on 15 healthy participants performing a MI task. The fMRI data provided global coverage of brain activity, thus allowing visualization of all potential brain regions activated and deactivated during task periods. Indeed, fMRI results from seven subjects included activation in the primary motor cortex and/or the pre-supplementary motor area during the rest periods in addition to the expected activation in the supplementary motor and premotor areas. Of these seven subjects, two showed inverse oxygenation with fNIRS. The proximity of the regions showing inverse oxygenation to the motor planning regions suggests that inverse activation detected by fNIRS may likely be a consequence of partial volume errors due to the sensitivity of the optodes to both primary motor and motor planning regions.